Sri Lanka’s elusive freshwater spiny eel, Macrognathus pentophthalmos (Teleostei: Mastacembelidae) - Sudasinghe, Hiranya; Ranasinghe, Tharindu; Perera, Rachith Priyankara; Rüber, Lukas (Zootaxa, 2024)
This study focuses on Macrognathus pentophthalmos, one of the two freshwater spiny eel species in Sri Lanka, which was once abundant in lowland floodplains. However, since the 1980s, this species has experienced a significant population decline, the causes of which remain unknown. It is presently assessed as Critically Endangered in the National Red List. Here, we report on a juvenile and an adult M. pentophthalmos discovered in the dry zone lowlands of the island. Using the mitochondrial cytochrome oxidase subunit 1 marker, we reveal subtle genetic differences between M. pentophthalmos and its Indian congener, M. aral. Additionally, we delve into the historical records of M. pentophthalmos in Sri Lanka, tracing its decline, and suggest strategic hotspots for further investigation into its current status. This study aims to contribute insights into the enigmatic decline of this species while shedding light on its genetic relationships and proposing targeted areas for conservation efforts.